2023
DOI: 10.3389/feart.2023.1107809
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on the long-term water balance in the Yarlung Zangbo basin

Abstract: The Himalayan and Tibetan Plateau (TP) region serves as the “Asian water tower”. Yarlung Zangbo basin (YZB) is one of most important major rivers originating from TP sustaining billions of lives in the downstream alluvial plain. Climate change has impacted the hydrological cycle in this alpine region; however, the temporal and spatial trends of runoff and the water balance has not been quantified adequately. Here, we have optimized the snowmelt module of the Soil and Water Assessment Tool (SWAT) for the YZB to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Notably, aligning with numerous global drought assessments, this research emphasizes that climatic factors are the most critical factors shaping the occurrence of drought [ 27 , 34 ]. In general, precipitation, temperature, precipitation days, and evaporation directly impact the water availability and water balance [ 31 ]. Research has shown that precipitation, precipitation days, and land use are the critical drought factors in the area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, aligning with numerous global drought assessments, this research emphasizes that climatic factors are the most critical factors shaping the occurrence of drought [ 27 , 34 ]. In general, precipitation, temperature, precipitation days, and evaporation directly impact the water availability and water balance [ 31 ]. Research has shown that precipitation, precipitation days, and land use are the critical drought factors in the area.…”
Section: Discussionmentioning
confidence: 99%
“…Soil texture, soil fertility, stream density, soil depth, soil moisture, and distance to rivers/irrigation are universal natural drought indicators used in drought assessment [ 16 , 17 , 29 , 30 ]. Climatic factors directly influence the climate of the region [ 31 ] and contribute to drought [ 32 , 33 ]. Various climatic factors, including precipitation, temperature, precipitation days, evaporation, and humidity, have been considered in drought assessment studies [ 2 , 13 , 27 , 34 ].…”
Section: Introductionmentioning
confidence: 99%